Evaluating the effect of chronic and continuous use of methadone on the glomerular filtration rate of patients receiving oral methadone (syrup) - Chegini, Valiollah Goudarzvand; Kazemifar, Amir Mohammad; Tavakolian, Amir Ershad; Karimi, Arian Ghannadi; Sofi, Arsalan Jamali Pour; Ipchian, Darya; Kamali, Sahand; Varkiani, Mehran Ebrahimi; Yazdi, Zohreh (Frontiers in Medicine, 2024)
IntroductionThis study systematically examines the effects of chronic oral methadone use on the glomerular filtration rate (GFR) in patients participating in methadone maintenance therapy (MMT) in Qazvin City, Iran. Methadone, a synthetic μ-opioid receptor agonist, is predominantly utilized for the management of opioid dependence and pain relief; however, there is growing concern regarding its potential nephrotoxic effects.MethodsAn observational cross-sectional study was executed involving 150 participants who had been on methadone syrup for a minimum duration of 2 years. Comprehensive data pertaining to demographic variables, methadone dosage, and serum creatinine levels were meticulously gathered at baseline, as well as at 3 and 6 months. GFR was calculated utilizing the Cockcroft-Gault formula.ResultsThe results demonstrate that, while the mean GFR values remained within the normal range, a significant correlation was observed between methadone dosage and a reduction in GFR; specifically, higher dosages were associated with lower GFR values. In contrast, the duration of methadone use did not significantly affect GFR.ConclusionThese findings indicate that, although methadone dosage may influence renal function, long-term methadone therapy does not inherently exacerbate the risk of chronic kidney disease (CKD) in this population. This underscores the critical need for diligent monitoring of methadone dosages to mitigate the risk of potential renal impairment and highlights the importance of further research into the long-term implications of methadone on renal health.